2002
DOI: 10.1021/la0115435
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Mobility and Electric Conductivity of Suspensions of Charge-Regulating Colloidal Spheres

Abstract: An analytical study of electrophoresis and electric conduction in a monodisperse suspension of spherical charge-regulating particles with an arbitrary thickness of the electric double layers is presented. The charge regulation due to association/dissociation reactions of ionogenic functional groups on the particle surface is approximated by a linearized regulation model, which specifies a linear relationship between the surface charge density and the surface potential. The effects of particle interactions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Moreover, Cdot are porous, that is, permeable to the fluid and ions. Therefore, the electrophoretic mobility of porous spherical Cdot under internal flow field contributes to the effective electrical conductivity of the water based Cdot nanofluid 48 . Thus, with increasing volume fraction, the overall electrical conductivity of the nanofluids increases.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Cdot are porous, that is, permeable to the fluid and ions. Therefore, the electrophoretic mobility of porous spherical Cdot under internal flow field contributes to the effective electrical conductivity of the water based Cdot nanofluid 48 . Thus, with increasing volume fraction, the overall electrical conductivity of the nanofluids increases.…”
Section: Resultsmentioning
confidence: 99%
“…However, the particles may influence the conductivity because they may produce significant electric fields in the suspension if their volume fraction is high enough. A recent analytical study [13] of conductivity and mobility of colloids led to closed-form equations for interacting particle suspensions but valid for low zeta potential (smaller than 25 mV). As we will see, the zeta potential is not low in our systems, so that here only a simple model will be used for conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…8 This conceptscharge compensations is well-developed and extensively modeled in colloid chemistry. 9, 10 Menon and Zydney suggested that it also applies to proteins and proposed a model to analyze the adjustment of charge of the macromolecule and the surrounding buffer upon annihilation of a positive charge from the surface of the protein.…”
Section: Introductionmentioning
confidence: 99%